Sustainable and circular agro-environmental practices: A review of the management of agricultural waste biomass in Spain and the Czech Republic. Issue 5 (May 2023) - Duque-Acevedo, Mónica; Ulloa-Murillo, Leidy Marcela; Belmonte-Ureña, Luis J; Camacho-Ferre, Francisco; Mercl, Filip; Tlustoš, Pavel
Sustainable and circular production models, such as the circular economy and circular bioeconomy, have become key mechanisms to leave behind the traditional linear model of food production. Under this approach and considering the waste biomass potential available in Spain and the Czech Republic, the main objective of this study is to analyse the most relevant aspects of the generation, use and regulation of agricultural waste biomass (AWB) in both countries. For this purpose, a scientometric analysis and systematic review of published research in the Scopus database were carried out. A complementary analysis of AWB management policies and regulations was also part of the methodology. The results show that Spain has published almost twice as much research as the Czech Republic. Furthermore, 91% of the retrieved research prioritizes the characterization and estimation of the potential of more than 15 AWB types. Among the main ones are olive residues, horticultural residues and wheat straw, which are used for producing organic amendments, bioenergy and biofuels. The results confirm that the reduction and valorization of AWB is an issue that has become more important in the last 13 years, mainly due to the policies and strategies for circular economy and circular bioeconomy. With this in mind, this study provides relevant information for governments on the aspects that need to be improved to advance in the valorization of AWB. This study also provides guidance to farmers on the reduction and/or recovery alternatives that they can implement to move towards sustainable and circular agriculture.